Child Mortality in Jumla District of Nepal: Trend and Socio-economic differentials. - Thapa, Narbada (Medical Journal of Shree Birendra Hospital, 1999)
Child Mortality in Jumla District of Nepal: Trend and Socio-economic differentials.